The Effect of Space Objects on Ionospheric Observations: Perspective of SYISR - Junyi Wang; Xinan Yue; Feng Ding; Baiqi Ning; Lin Jin; Changhai Ke; Ning Zhang; Junhao Luo; Yonghui Wang; Hanlin Yin; Mingyuan Li; Yihui Cai (Remote Sensing, 2022)
Space objects around the Earth are a potential pollution source for ground-based radio observations. The Sanya incoherent scatter radar (SYISR) is a newly built active digital phased array, all solid-state transmitting and digital receiving incoherent scatter radar in Sanya (18.3°N, 109.6°E), with the main purpose of ionospheric monitoring and investigations. In this study, we presented the effect of the greatly increased number of space objects on ionospheric observations through SYISR. Firstly, we showed the space object pollution on the range-time-intensity (RTI), autocorrelation function (ACF)/power spectra, and ionosphere parameter of SYISR measurements. An altitude of around 600 km is the region where space objects occur most frequently. Then, we eliminated the space object pollution using the traditional smallest of constant-false-alarm-rate (SO-CFAR) algorithm. However, pollution from smaller space objects remains, whose reflected echo is comparable to or lower than the background ionosphere, which results in unrealistic retrieved ionospheric electron density. Furthermore, we quantitatively assessed the space object effect based on the current space object orbit database and simulation. The pollution should linearly increase with the increase in the number of space objects in the future. Among the space objects, whose radar cross section (RCS) and orbit information are now published, there still exist ~9000 (~37% of the total number) space objects, whose effect is difficult to eliminate. This study is beneficial to the data process of SYISR and has implications for similar types of ionospheric observations by radar.